EFEKTIFITAS PENERAPAN QANUN NOMOR 14 TAHUN 2003 TENTANG KHALWAT DI KABUPATEN ACEH BESAR - Faisal Faisal (Islam Futura, 2013)
The Government of Aceh form Qanun No. 14 of 2003 on Klalwat (seclusion) by Regulation No. 5 of 2000 on the implementation of Shari'ah. In the regulation stated that the Islamic Sharia Qanun No. 14 of 2003 on Seclusion / Impropriety, defined as "the act of seclusion between two people mukallaf or more of the opposite sex who is not mahram or without marriage. Based on the research conducted through the application of Qanun No. 14 of 2003 approach on khlawat (sordid) has brought some changes in the social order of Aceh Besar. The fundamental change can be seen from the reducing of adultery level in society. It means that the implementation of the Qanun No. 14 of 2003 on Khalwat in Aceh Besar effective.